Synthesis of Biodiesel from Used Cooking Oil Using Composite Photocatalyst from Milkfish Bones And TiO2 - Adiwibowo, Muhammad Triyogo; Wardalia, Wardalia; Kustiningsih, Indar; Daimah, Radhini Salma; Nugroho, Adhitiya Aprianto; Maemunah, Shiva; Alawiyah, Rizqi (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2025)
The increasing number of vehicles in Indonesia has increased air pollution and fuel consumption. The fuels commonly used come from fossil, the availability of which is limited. One solution that can be applied is switching to alternative energy, such as biodiesel from vegetable oils, including used cooking oil. This study investigates the effect of reactant ratio, catalyst weight, UV exposure, and catalyst reusability on biodiesel yield and characteristics (density and viscosity) according to Indonesian national standards (SNI). The method used involves the impregnation of CaO catalysts with TiO2 photocatalysts and simultaneous transesterification-esterification reaction for biodiesel production, with oil to methanol molar ratios of 1:6, 1:9, and 1:12 and catalyst weights of 3, 5, and 7%. The results showed that the best product had a yield of 90.6%, a density of 882 kg/m³, and a viscosity of 2.45 mm2/s at a reactant ratio of 1:9 and a catalyst weight of 5%, with UV exposure for 4 hours at a temperature of 65°C. XRD and EDS analysis revealed the presence of CaO-TiO2 compounds in the synthesized photocatalyst, and the GCMS analysis shows that FAME (fatty acid methyl ester) content in the biodiesel is more than 96%.